Gold nanoclusters as prospective carriers and detectors of pramipexole. Issue 27 (5th May 2021) - Si, Nguyen Thanh; Nhung, Nguyen Thi Ai; Bui, Thanh Q.; Nguyen, Minh Tho; Nhat, Pham Vu
Abstract : Gold clusters as prospective carriers and detectors of pramipexole. Abstract : Pramipexole (PPX) is known in the treatment of Parkinson's disease and restless legs syndrome. We carried out a theoretical investigation on pramipexole–Au cluster interactions for the applications of drug delivery and detection. Three Au N clusters with sizes N = 6, 8 and 20 were used as reactant models to simulate the metallic nanostructured surfaces. Quantum chemical computations were performed in both gas phase and aqueous environments using density functional theory (DFT) with the PBE functional and the cc-pVDZ-PP/cc-pVTZ basis set. The PPX drug is mainly adsorbed on gold clusters via its nitrogen atom of the thiazole ring with binding energies of ca. −22 to −28 kcal mol −1 in vacuum and ca. −18 to −24 kcal mol −1 in aqueous solution. In addition to such Au–N covalent bonding, the metal–drug interactions are further stabilized by electrostatic effects, namely hydrogen-bond NH⋯Au contributions. Surface-enhanced Raman scattering (SERS) of PPX adsorbed on the Au surfaces and its desorption process were also examined. In comparison to Au8, both Au6 and Au20 clusters undergo a shorter recovery time and a larger change of energy gap, being possibly conducive to electrical conversion, thus signaling for detection of the drug. A chemical enhancement mechanism for SERS procedure was again established in view of the formation of nonconventional hydrogen interactions Au⋯H–N. The binding of PPX to a gold cluster is expected to be reversible and triggered by the presence of cysteine residues in protein matrices or lower-shifted alteration of environment pH. These findings would encourage either further theoretical probes to reach more accurate views on the efficiency of pramipexole–Au interactions, or experimental attempts to build appropriate gold nanostructures for practical trials, harnessing their potentiality for applications.